Cardiovascular risk factors and carotid intima‐media thickness are associated with lower cognitive performance in HIV‐infected patients. Issue 3 (21st September 2012) - Fabbiani, M; Ciccarelli, N; Tana, M; Farina, S; Baldonero, E; Di Cristo, V; Colafigli, M; Tamburrini, E; Cauda, R; Silveri, MC; Grima, P; Di Giambenedetto, S
<x xml:space="preserve">Abstract</x> Objectives The aim of the study was to investigate the relationship between metabolic comorbidities, cardiovascular risk factors or common carotid intima‐media thickness (cIMT) and cognitive performance in HIV‐infected patients. Methods Asymptomatic HIV‐infected subjects were consecutively enrolled during routine out‐patient visits at two clinical centres. All patients underwent an extensive neuropsychological battery and assessment of metabolic comorbidities and cardiovascular risk factors. Moreover, cIMT was assessed by ultrasonography. Cognitive performance was evaluated by calculating a global cognitive impairment (GCI) score obtained by summing scores assigned to each test (0 if normal and 1 if pathological). Results A total of 245 patients (median age 46 years; 84.1% with HIV RNA < 50 copies/mL; median CD4 count 527 cells/μL) were enrolled in the study. Cardiovascular risk factors were highly prevalent in our population: the most frequent were dyslipidaemia (61.2%), cigarette smoking (54.3%) and hypertension (15.1%). cIMT was abnormal (≥ 0.9mm) in 31.8% of patients. Overall, the median GCI score was 2 [interquartile range (IQR) 1–4]; it was higher in patients with diabetes (P = 0.004), hypertension (P = 0.030) or cIMT ≥ 0.9 mm (P < 0.001). In multivariate analysis, it was confirmed that diabetes (P = 0.007) and cIMT ≥ 0.9 mm (P = 0.044) had an independent association with lower cognitive performance. In an analysis of patients on combination antiretroviral therapy (cART), abacavir use was independently associated with a better cognitive performance (P = 0.011), while no association was observed for other drugs or neuroeffectiveness score. Conclusions Diabetes, cardiovascular risk factors and cIMT showed a strong association with lower cognitive performance, suggesting that metabolic comorbidities could play a relevant role in the pathogenesis of HIV‐associated neurocognitive disorders in the recent cART era.